800 Celebrate CNY joint celebration - UMP, PNC
Over 800 people from all walks of life attended the Chap Goh Mei dinner, jointly organized by the Chinese Cultural Association, and Universiti Malaysia Pahang’s (UMP) Department of Students Affair & Alumni, held at the Mexica Seafood Restaurant in Kuantan on February 28.